The effects of green product positioning and green marketing strategies towards customers purchase intention in Malaysia - Sathiswaran Uthamaputhran (2013)
The main purpose of this study is to investigate the effectiveness of product positioning (functional attributes and emotional benefits) and how it is reflected to the customer's purchase intention. The study is to examine the green marketing strategies and the effects of these variables (beliefs, eco-Labelling, product attitudes and green advertising). Elaboration Likelihood Model (ELM)and Effect-Reason-Involvement model (ARI) were used to make the study stronger and accurate. This paper contitutes the qualitative results of customers through sef-administered questionnaires with the size of 400 respondents and 200 were returned. This study confirms that there is an affecting between product positioning and green marketing strategies. This study also confirmed that green marketing strategies affects the customer's purchase intention towards green products.